Governing Hajj: Politics of Islamic Pilgrimage Services in Indonesia Prior to Reformasi Era - Ichwan, Moch Nur (Al-Jamiah: Journal of Islamic Studies, 2008)
This article highlights that the hajj (Islamic pilgrimage to Mecca) involves not only religious devotion, but also religious tourism and its associated business, necessary to deal with massive parties of pilgrims, embracing trans-national relations, central and local governments, flight and other travel agencies, pilgrimage guidance units, catering agencies and hotels to the pilgrims themselves in its scope. The aim of this article is to analyse the politics of hajj services, which was carried out mainly through the placing of this pilgrimage under government control, leading to the assumption of its monopoly by the government during the New Order period. Although it will focus on Soeharto period, there will be some discussions on this subject during the colonial and early post-colonial periods to trace the genealogy of government control of hajj pilgrimage (and âumrah, known also as âsmall hajjâ), especially during the New Order.Â  The author argues that the complexities of hajj (and âumrah) services were not so much caused by religious aspect but rather by political and economic motives.